3D time-dependent hydrodynamical and radiative transfer modeling of Eta Carinae's innermost fossil colliding wind structures. Issue Volume 14:Issue S346(2019) (August 2018) - Madura, Thomas; Gull, T. R.; Clementel, N.; Corcoran, M.; Damineli, A.; Hamaguchi, K.; Hillier, D. J.; Moffat, A. F. J.; Richardson, N.; Weigelt, G.
Abstract: Eta Carinae is the most massive active binary within 10, 000 light-years. While famous for the largest non-terminal stellar explosion ever recorded, observations reveal a supermassive (∼120 M⊙ ) binary consisting of an LBV and either a WR or extreme O star in a very eccentric orbit ( e =0.9) with a 5.54-year period. Dramatic changes across multiple wavelengths are routinely observed as the stars move about in their highly elliptical orbits, especially around periastron when the hot (∼40 kK) companion star delves deep into the denser and much cooler (∼15 kK) extended wind photosphere of the LBV primary. Many of these changes are due to a dynamic wind-wind collision region (WWCR) that forms between the stars, plus expanding radiation-illuminated fossil WWCRs formed one, two, and three 5.54-year orbital cycles ago. These fossil WWCRs have been spatially and spectrally resolved by the Hubble Space Telescope /Space Telescope Imaging Spectrograph ( HST /STIS) at multiple epochs, resulting in data cubes that spatially map Eta Carinae's innermost WWCRs and follow temporal changes in several forbidden emission lines (e.g. [Fe iii ] 4659 Å, [Fe ii ] 4815 Å) across the 5.54-year cycle. We present initial results of 3D time-dependent hydrodynamical and radiative-transfer simulations of the Eta Carinae binary and its WWCRs with the goal of producing synthetic data cubes of forbidden emission lines for comparison to the available HST /STIS observations. Comparison of the theoretical models to the observations reveals important details about the binary's orbital motion, photoionization properties, and recent (5–15year) mass loss history. Such an analysis also provides a baseline for following future changes in Eta Carinae, essential for understanding the late-stage evolution of a nearby supernova progenitor. Our modeling methods can also be adapted to a number of other colliding wind binary systems (e.g. WR 140) that are scheduled to be studied with future observatories (e.g. the James Webb Space Telescope).